Hybrid Digital Replication Rights: Recalibrating Identity Protection in the Indonesian Legal System through the Perspective of Lex AI - Kirana Hamonangan, Marcellius; Gunadi, Ariawan (Al-Risalah, 2026)
Modern AI systems are increasingly capable of replicating a person’s voice, facial resemblance, body movements, and behavior without the consent of the subject in question. Existing legal frameworks—including privacy laws, copyright laws, and publicity rights—provide only partial protection and are not yet sufficient to address AI-based identity duplication. In Indonesia, the absence of explicit provisions in Law No. 27 of 2022 on Personal Data Protection and the Copyright Law regarding synthetic personas creates a legal gap that could lead to uncertainty as well as economic and reputational harm to individuals. This article analyzes the legal implications of identity replication enabled by AI and, for the first time, introduces the concept of Hybrid Digital Replication Rights (DRR) as a new legal framework for digital identity protection. Unlike traditional production-based approaches in intellectual property law, DRR adopts replication-based protection, which is triggered when synthetic outputs bear substantial resemblance to identifiable individuals and pose a risk of tangible harm.  DRR is designed with limited economic components valid for the duration of a person’s lifetime plus seventy years, as well as a non-transferable moral core rooted in the principle of human dignity. Referring to Lex AI’s theory of Private Ordering by Design, this article asserts that identity protection must be integrated into the technical architecture of AI systems. Thus, this article makes a conceptual contribution by formulating DRR as a normative–technical legal framework within the context of the Indonesian legal system.